Okoboji wetlands : a lesson in natural history - Lannoo, Michael J. (Bur oak original., 1996)
Lake Okoboji in northwest Iowa is the jewel of the Iowa Great Lakes. A region of wetlands formed by prairie potholes, the area is rich with lakes, sloughs, fens, creeks, prairies, and kettleholes. In this readable and beautifully illustrated volume, Michael Lannoo presents an extensive natural history of Okoboji and its cherished wetlands that examines that world of our grandparents, compares it to today's world, and extrapolates to the world of our grandchildren.